COVID-19 and all-cause-mortality; differential trends between countries and selected states of India - Menon, Jaideep C.; Suseela, Rakesh P.; Bharti, Omesh K.; Mishra, Kaushik; Swain, Basanta; Raina, Sunil; John, Denny; Janakiram, Chandrasekhar; Banerjee, Amitava (International Journal Of Community Medicine And Public Health, 2021)
By 22nd January 2021, the Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) virus had infected over 98 million and 10.6 million individuals globally and in India, with 1.7 million and 153, 067 deaths, respectively. Case Fatality rates (CFR) due to coronavirus disease 2019 (COVID 19) have varied significantly between countries. In order to understand the true impact of the pandemic, we should report coronavirus (COVID-19) mortality in the context of all-cause and non-COVID-19 mortality, and compare with previous years. The consequences of the pandemic have been, and will be, different in different settings within and across countries. To compare the all-cause mortality in the year 2020 with previous years in three selected states of India correlate it to the burden of COVID19 and compare all-cause mortality between three states of India to four high income countries. We provide quantitative data in three states across India (Himachal Pradesh, Kerala and Odisha) and compare with high-income countries to illustrate the importance of context-specific data monitoring and public health responses. There was a 1.9% increase in deaths, with 2.8% decrease in births in 2020, compared to 2019 in Himachal Pradesh, 13.3 and 9.2% decrease in Kerala and 16.7% and 21.4% decrease in Odisha. There was a direct correlation of all cause mortality to CFR on comparison between three states of India and despite the enormous burden of COVID19 in India all-cause mortality was lower compared to previous years in addition to the CFR due to COVID 19 being lower than in selected HICs.